2017
DOI: 10.1016/j.atherosclerosis.2017.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Opposing effects of rheumatoid arthritis and low dose prednisolone on arginine metabolomics

Abstract: Rheumatoid arthritis patients have higher concentrations of ADMA and MMA, inhibitors of endothelial function. Chronic, but not acute, prednisolone therapy is associated with a lower ADMA concentration, suggesting a salutary effect of long-term glucocorticoid treatment on endothelial function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 47 publications
2
18
0
Order By: Relevance
“…Of interest, polyunsaturated acyl LPC and LPE presented an anti-inflammatory effect on animal models [60]. The effect of low dose GC (<10 mg/day) on arginine metabolism and cardiovascular risk in RA patients was also studied [61]. This study from Australia that included 36 RA patients, 18 of which were on GC (GC users) and 18 that were not receiving GC (non-GC-users), found that asymmetric dimethyl arginine (ADMA) and symmetric dimethyl arginine (SDMA) levels were lower in patients on chronic GC compared to non-GC users, suggesting that long-term treatment with GC had an improved endothelial function and a cardiovascular protective effect.…”
Section: Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of interest, polyunsaturated acyl LPC and LPE presented an anti-inflammatory effect on animal models [60]. The effect of low dose GC (<10 mg/day) on arginine metabolism and cardiovascular risk in RA patients was also studied [61]. This study from Australia that included 36 RA patients, 18 of which were on GC (GC users) and 18 that were not receiving GC (non-GC-users), found that asymmetric dimethyl arginine (ADMA) and symmetric dimethyl arginine (SDMA) levels were lower in patients on chronic GC compared to non-GC users, suggesting that long-term treatment with GC had an improved endothelial function and a cardiovascular protective effect.…”
Section: Drugsmentioning
confidence: 99%
“…This study from Australia that included 36 RA patients, 18 of which were on GC (GC users) and 18 that were not receiving GC (non-GC-users), found that asymmetric dimethyl arginine (ADMA) and symmetric dimethyl arginine (SDMA) levels were lower in patients on chronic GC compared to non-GC users, suggesting that long-term treatment with GC had an improved endothelial function and a cardiovascular protective effect. by modulating arginine metabolism [61].…”
Section: Drugsmentioning
confidence: 99%
“…Negative regulation of NO synthesis can also be mediated through overproduction of methylated arginine analogues such as ADMA. Recently, many clinical studies have demonstrated that plasma levels of ADMA were elevated in RA patients regardless of the presence of cardiovascular disease [55][56][57][58][59][60][61][62][63][64][65][66][67]. Furthermore, ADMA has been reported to be related to indices of endothelial dysfunction or subclinical atherosclerosis in some [56,65,68], but not all, conducted studies [58,60,61,67,68].…”
Section: Asymmetric Dimethylarginine (Adma)mentioning
confidence: 99%
“…Finally, it has been shown that TNF inhibitors improved the L-arginine/ADMA ratio due to the increase in L-arginine, and the L-arginine/ADMA ratio was longitudinally related to PWV after initiation of anti-TNF-α therapy [58]. Acute and chronic oral treatments with glucocorticoids have also different effects on arginine metabolites; while acute prednisolone therapy has no impact, chronic prednisolone treatment reduces ADMA and SDMA plasma concentrations [57].…”
Section: Rheumatoid Arthritis (Ra)mentioning
confidence: 99%
“…This might account for the reduced coronary flow reserve, and consequent increased risk of ischaemic heart disease, reported in patients with rheumatoid arthritis and other similar autoimmune conditions [68]. In addition to the potential role of inflammatory pathways and traditional cardiovascular risk factors, the accumulation of the potent endogenous inhibitor of eNOS synthase, asymmetric dimethylarginine (ADMA), might also play a role in the pathogenesis of endothelial dysfunction in rheumatoid arthritis [69][70][71].…”
Section: Rheumatoid Arthritis: a Human Model Of Premature Vascular Agmentioning
confidence: 99%